Business Expansion Efforts Through Empowering Business Groups With Lee Min Book - Heidy Paramitha Devi; Puji Nurhayati; Hapsari Endras Ayu Novita; Mutiatun Nur Fauziah; Cindy Violita; Anisa Ayera (UNUSA Press, 2021)
The implementation of this Community Service is an effort to develop the Family Welfare Development Group Business in Cileng Village, Poncol District, Magetan Regency to be able to increase product competitiveness through improved business management and business legality. The main problems of partners are: 1) the production of handicrafts in the form of plastic glass lip recycling bags still using the made by order system, 2) from the financial side there is no good record, the capital used still comes from the group cash, 3) limited marketing only in the surrounding community. In line with the problems faced by these partners, efforts that can be made are assistance in business development starting from marketing, business legality and bookkeeping. The methods used by the team are socialization, training and mentoring. The results of the Community Service Program are: 1) The Group Business has a Business Permit Number which means that with this legality it will make it easier for partners to get capital, increase public confidence in the products produced, 2) There is an increase in the knowledge and skills of partners in recording daily finances simply , making it easier for partners to evaluate production activities, evaluate income and expenditure, 3) Availability of product logos and fan pages, of course this will increase the selling value of partner products and expand the target market.